Casa GGG, México DF (México) - Kalach, Alberto (2001)
Vivienda para un empresario del espectáculo en un solar cercano a un campo de golf
Keywords: MEXICO; MÉXICO DF; VIVIENDAS UNIFAMILIARES; CONSTRUCCION; HORMIGON ARMADO